Solid Waste Disposal and Extent of Selected Heavy Metals in Fadama Area of Sokoto City, Nigeria - Yusuf Sarkingobir; Umar Tambari; Aminu Umar Imam; Marwanu Abubakar; Mustapha Sahabi (BIORE Scientia Publisher, 2023)
This study was carried out with the purpose of assessing solid waste disposal and levels of heavy metals in Fadama area of Sokoto city. A survey using questionnaire and atomic absorp-tion spectroscopy was employed for the study. The descriptive statistics and X2 test were done. The types of pollution noticed include: land (40.0%), air (40.0%), and water (20.0%). The possible causes of the pollution include, mostly open dumping of solid waste (41.7%), then open defecation (33.3%), and lastly burning (25.0%). Spread of diseases was most (40.0%) perceived effect, then effect on children (20.0%) and gastroenteritis (20.0%). Other effects are: sickness (13.3%) and accidents (6.7%). The efforts to address the waste disposal are: burning (60.0%), pushing it away from road (20.0%) and provision of containers (20.0%). Effort did by the government involves, promising to bring con-tainers (30.0%), and doing nothing (70.0%). Wastes found are: plastics (70.0%), organic and defeca-tions (23.3%), metal and relations. The heavy metals analysis shows, the lead ranges from 5.1 ± 1.2 to 10.0 ± 0.80 (ppm); chromium ranges from 0.59 ± 0.01 to 2.10 ± 0.02 (ppm); zinc ranges from not detected to 0.81 ± 0.3 (ppm); cadmium from 0.25 ± 0.02; and mercury ranges from 0.95 ± 0.02 to 10.20 ± 0.11 (ppm). There is poor waste management in an agricultural area, a trend that can seep harmful chemicals to be taken up by plants to the upward food chain/web, coupled with other harmful ef-fects of waste such as instigation of diseases and environmental degradation.